Durabilidade de Revestimentos Exteriores de Parede em Monocamada - Marisa Betânia de Oliveira Antunes Quintela (2006)
The increasing concerns with costs rationalization, fulfilment of deadlines, quality of work, cleaning-up related questions and space availability at the construction site, boosted the usage of industrial mortars.One coat rendering mortar for external use is a designed rendering mortar applied in one coat, which fulfils all the functions of a multicoat system used externally and is usually specially coloured.To ensure an adequate performance of the rendering it is essential to fulfil the requirements including all the phases of the process, from the design till in-use conditions.Regardless of age, good and bad examples of one coat rendering mortar performance can be found in Portuguese buildings.Comparatively to multicoat rendering system, the experience on the application of such products in Portugal, is not yet long enough to conclude about its durability.With the purpose of testing the durability of such mortar, a vast experimental campaign was conducted, in the LFC. The intention was to characterize the most significantly degradationagents; to evaluate the possibility of, with laboratory testing, identify performance-over-time functions; to evaluate its capacity to satisfy the essential requirements, after being submitted toageing procedures.This work's methodology consisted in evaluating the properties of the rendering at its initial state and after having been submitted to artificial accelerated ageing procedures. Three different procedures have been developed.Natural ageing tests were also used in order to adjust the performance-over-time functions, which are indispensable for service life prediction. Due to the limited time available to carry outthis work, the rendering mortar was only tested with a natural exposure time of 21 months.This work aims to contribute to a better understanding of the one coat rendering mortar's performance and its evolution over time in terms of water permeability, adhesion and colour stability.Keywords: External renders, One-coat rendering mortar, Durability, Service life, Artificial accelerated ageing, Natural ageing test.